Laparoscopic pancreatectomy for cancer in high volume centers is associated with an increased use and fewer delays of adjuvant chemotherapy. Issue 4 (April 2021) - Kutlu, Onur C.; Vega, Eduardo A.; Salehi, Omid; Lathan, Christopher; Kim, Sunhee; Krishnan, Sandeep; Stallwood, Christopher; Kozyreva, Olga; Conrad, Claudius
Abstract: Background: This study aimed to investigate the relationship between hospital case volume, surgical approach and AC-use in patients who underwent pancreatectomy for pancreatic ductal adenocarcinoma (PDAC). Methods: Patients were divided into quartiles by institutional pancreatectomy case volume, resection type (pancreaticoduodenectomy [PD], distal pancreatectomy [DP], or total pancreatectomy [TP]) and surgical approach (laparoscopic vs. open). The rates and contributing factors of AC administration and delay >90 days were compared among volume quartiles and surgical approaches. Results: This study identified 23, 494 patients who had undergone pancreatectomy for PDAC between 2010 and 2016 and met inclusion criteria. After correcting for confounders, compared to low volume hospitals patients at high-case-volume hospitals had the highest rates of AC administration after PD and DP. Moreover, compared to open surgery for all resection types, laparoscopic surgery was associated with a higher rate of AC use at high and highest-case-volume hospitals and less delay to chemotherapy at high-volume hospitals. For DP, laparoscopic approach had a positive impact on AC delay >90-day at the highest volume institutions only. Conclusions: Laparoscopic surgery for pancreatic cancer leads to higher utilization and lower probability of delay of AC in high and highest volume hospitals.